A beaded romance: 26 bead weaving patterns and projects for gorgeous jewelry - Wiese, Kelly (Ohio: David and Charles, 2013)
Includes index.
Keywords: Jewelry making; Beadwork patterns; Weaving -- Patterns; Beadwork; Weaving